Subtle Role for Adenylate Kinase 1 in Maintaining Normal Basal Contractile Function and Metabolism in the Murine Heart - Zervou, Sevasti; McAndrew, Debra J.; Whittington, Hannah J.; Lake, Hannah A.; Park, Kyung Chan; Cha, Kuan Minn; Ostrowski, Philip J.; Eykyn, Thomas R.; Schneider, Jürgen E.; Neubauer, Stefan; Lygate, Craig A. (Frontiers in Physiology, 2021)
Aims: Adenylate kinase 1 (AK1) catalyses the reaction 2ADP ↔ ATP + AMP, extracting extra energy under metabolic stress and promoting energetic homeostasis. We hypothesised that increased AK1 activity would have negligible effects at rest, but protect against ischaemia / reperfusion (I/R) injury. Methods and results: Cardiac-specific AK1 overexpressing mice (AK1-OE) had 31% higher AK1 activity (P=0.009), with unchanged total creatine kinase and citrate synthase activities. Male AK1-OE exhibited mild in vivo dysfunction at baseline with lower LV pressure, impaired relaxation, and contractile reserve. LV weight was 19% higher in AK1-OE males due to higher tissue water content in the absence of hypertrophy or fibrosis. AK1-OE hearts had significantly raised creatine, unaltered total adenine nucleotides, and 20% higher AMP levels (P=0.05), but AMP-activated protein kinase was not activated (P=0.85). 1H-NMR revealed significant differences in LV metabolite levels compared to wild-type, with aspartate, tyrosine, sphingomyelin, cholesterol all elevated, whereas taurine and triglycerides were significantly lower. Ex vivo global no-flow I/R, caused four-of-seven AK1-OE hearts to develop terminal arrhythmia (cf. zero WT), yet surviving AK1-OE hearts had improved functional recovery. However, AK1-OE did not influence infarct size in vivo and arrhythmias were only observed ex vivo, probably as an artefact of adenine nucleotide loss during cannulation. Conclusions: Modest elevation of AK1 may improve functional recovery following I/R, but has unexpected impact on LV weight, function and metabolite levels under basal resting conditions, suggesting a more nuanced role for AK1 underpinning myocardial energy homeostasis and not just as a response to stress.